Collaborative Speed Planning Algorithm with Centralized Decision-Making for Virtual Coupling of Autonomous-Rail Rapid Tram - HUANG Qiang; LI Cheng; TANG Xiang; YUAN Xiwen; HE Chuan; HUANG Zhikun (Kongzhi Yu Xinxi Jishu)
The virtual coupling technology for autonomous-rail rapid trams can effectively realize optimal dynamic matching between vehicle capacity and passenger flow. This paper addresses the challenges of control stability and synchronous start-stop operation at platforms during the variable-speed operation of tram groups, based on in-depth analyses focusing on the traction and braking characteristics, vehicle kinematics, and dynamics models of autonomous-rail rapid trams. A collaborative speed planning algorithm with centralized decision-making was proposed for the virtual coupling of autonomous-rail rapid trams, targeting the core requirements for group operation: safety, comfort, punctuality, and efficient operation at platforms. Additionally, an optimal solution model was constructed to calculate the optimal time series for running displacements, speeds, and accelerations of trams within virtual coupling groups. Testing and verification were conducted with two autonomous-rail rapid trams on a field track, yielding impact rates of equal to or less than 0.3 m/s3, punctuality errors under 3 s, starting time differences of less than 1 s, stopping time differences of less than 2 s, and stopping control errors of less than 0.1 m during group operation. The results demonstrate that this method can effectively meet the actual operational requirements of autonomous-rail rapid trams, highlighting its excellent engineering application value and potential for popularization.